Pengaruh Kebijakan Perpajakan pada Perencanaan Pajak dengan Sanksi Administrasi sebagai Pemoderasi - I Putu Edy Arizona (Jurnal Inovasi Akuntansi)
This study aims to determine and obtain empirical evidence of the effect of tax policy on individual taxpayer tax planning, with tax sanctions as a moderating variable at the South Badung Tax Service Office. The research population amounted to 77,248 taxpayers, and we obtained a sample of 100 taxpayers. The analysis technique used in this research is moderated regression analysis (MRA). The results showed that tax policy had a positive effect on tax planning, and administrative sanctions were unable to moderate tax policy on tax planning.